TOTAL ANTIOXIDANT, RENAL FUNCTION TEST IN IRAQI WOMEN WITH BREAST CANCER - Buraq Mashaan Attallah; Wajih Younes Al-Ani; Nafea S Alboaisa (Scholar Express Journals, 2022)
Cancer is a collection of disorders characterized by uncontrolled cell growth, with breast cancer being the most common among women. The purpose of this study is to look at renal function and total antioxidants in Iraqi women who have been diagnosed with breast cancer. Three groups of Iraqi women were chosen: group I (50 healthy women), group II (32 new patients diagnosed with breast cancer but not getting chemotherapy), and group III (43 patients who received chemotherapy). The study has included the measurement of two biochemical variables, including total antioxidant and renal function tests. The results showed a significant decrease in creatinine between groups I and III. The results also showed a significant increase (P <0.05) between the group I and the group II in all antioxidants. The findings also showed a significant increase in antioxidants between the groups I and II. There were also some nonsignificant results between each of the groups I and III, which included urea and creatinine. There were some non-significant results between both groups I and III in urea.>
Keywords: antioxidants; breast cancer; renal function test; Statistical analysis